Harapan bagi yang Putus Asa - Petrus Go Twan An (Seri Filsafat Teologi, 2021)
In this article, the author offers a schematic presentation from the perspective of Catholic Moral Theology on hope as a theological virtue. The author also provides important notes on pastoral ministry for people who seek assistance pertaining to their difficult and desperate situations.